A tool for functional following and improvement interphase during the retraining of injured football ́s player - Gómez Piqueras, P.; Ortega Jiménez, J. M.; Sainz de Baranda Andújar, P. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2013)
Conscious about the importance of a sure injured footballer ́s returnto play, and knowing the complex process of decision relative to theideal moment for the return in group training, we present a tool ofwork and register that while permitting control us the follow-up andthe evolution of our sportsman, complement to the objectives tests remainders carried out (conditional, functional, psychological, ...)collaborating in the determination of the suitable moment of return.